Association between MRI-detected knee joint regional effusion-synovitis and structural changes in older adults: a cohort study. Issue 3 (30th December 2014) - Wang, Xia; Blizzard, Leigh; Halliday, Andrew; Han, Weiyu; Jin, Xingzhong; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract : Objective: To describe the cross-sectional and longitudinal associations between knee regional effusion-synovitis and structural changes in older adults. Methods: A total of 977 subjects were randomly selected from the local community (mean 62 years, 50% female) at baseline and 404 were followed up 2.6 years later. T2-weighted MRI was used to assess knee effusion-synovitis in four subregions: suprapatellar pouch, central portion, posterior femoral recess and subpopliteal recess. Knee cartilage defects, cartilage volume and bone marrow lesions (BMLs) were measured using MRI at baseline and follow-up. Results: Cross-sectionally, effusion-synovitis in most subregions was significantly associated with a higher risk of cartilage defects, BMLs and reduced cartilage volume. Longitudinally, suprapatellar pouch effusion-synovitis at baseline predicted an increase in cartilage defects (p<0.01), loss of cartilage volume (p=0.04) and an increase in BMLs (p=0.02) in multivariable analyses. The significant associations of effusion-synovitis with cartilage volume and BMLs disappeared after adjustment for cartilage defects. Effusion-synovitis in whole knee joint (p<0.01) and subpopliteal recess (p<0.05) was consistently associated with longitudinal changes in cartilage defects but not in cartilage volume and BMLs. Conclusions: There are independent associations between knee joint effusion-synovitis and knee cartilage defects in both cross-sectional and longitudinal analyses, suggesting a potential causal relationship. The associations of effusion-synovitis with BMLs and cartilage volume were largely dependent on cartilage defects, suggesting potential causal pathways.